Polycarboxylate ethers: The key towards non-toxic TiO2 nanoparticle stabilisation in physiological solutions - Koch, S.; Kessler, M.; Mandel, Karl; Dembski, S.; Heuze, Karine; Hackenberg, S. (Colloids and Surfaces B: Biointerfaces, 2016)
Stable, non-agglomerated TiO2 nanoparticle (NP) dispersions are a crucial requirement for an accurate NP dosing in in vitro and in vivo experiments. In this study self-synthesised TiO2 NPs were stabilised in three different cell culture media (DMEM, RPMI, BEGM) with the help of stabilising agents. Cell culture tested stabilisers (bovine serum albumin, fetal bovine serum) were compared to non-tested commercial products which are commonly utilized in the cement industry (Melflux® 4930 F, Melpers® 4343, Sika® ViscoCrete®-10110178). For a quantitative evaluation and comparison of the degree of stabilisation, a sedimentation study using UV absorbance spectroscopy was carried out and the agglomerate size was measured via dynamic light scattering. The cytotoxicity of the novel surfactants and stabilised NPs was examined in a head and neck squamous cell carcinoma-derived FaDu cell line and in human mesenchymal stem cells. We successfully stabilised TiO2 NPs with Melflux® 4930 F in each cell culture medium, achieving perfect stability over at least one day and agglomerate sizes of less than 100 nm, while the cytotoxicity of the NPs was not affected.
CRIS-Team Scopus Importer:2020-04-02
Keywords: Cell culture media; Cytotoxicity; Melflux; Stabilisation; Surfactants; TiO